To find the expression that equals 2B - A in standard form, we need to substitute the values of B and A into the expression and simplify.
Given:
B = 1 - 6w^2
A = 1 + w
Now, substitute the values of B and A into the expression 2B - A:
2(1 - 6w^2) - (1 + w)
Simplify the expression:
2 - 12w^2 - 1 - w
Combine like terms:
-12w^2 - w + 1
So, the expression that equals 2B - A in standard form is -12w^2 - w + 1.
If B, equals, 1, minus, 6, w, squaredB=1−6w
2
and A, equals, 1, plus, w, commaA=1+w, find an expression that equals 2, B, minus, A2B−A in standard form.
1 answer